2019
DOI: 10.11648/j.ijll.20190703.12
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Graduation Resources in Concession Addresses

Abstract: The concession address is generally considered as the final swan song of a lost campaign, communicating the defeated presidential nominee's thankfulness and gratitude to his or her supporters. Transcripts, videos or audios of concession addresses are easily accessible to the public via internet, television or even radio. With its easy accessibility, the concession address plays a significant part and has a high profile in the public's daily life. Nonetheless, the researches on concession addresses are few and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
1
0
2
Order By: Relevance
“…(Martin & White, 2005) 2.2 Applied research on appraisal system As the appraisal system is very important to explore the interpersonal meaning of discourses, the appraisal system has gained wide attention from scholars at home and abroad since put forward. As one of the three subsystems of the appraisal system, the graduation system is also widely used in various discourses, such as academic discourses (Xie, 2017;Wang & Guan, 2016), debate discourses (Dong, 2012), literary texts (Fu & Fu, 2009), news discourses (Jiang & Xu, 2019), translation discourses (Munday, 2015;Shi & Gao, 2019), concession addresses (Li & Li, 2019). For example, Wang & Guan (2016) made a comparative analysis of graduation resources used in English and Chinese linguistics book reviews, and found that there are a large number of graduation resources in English and Chinese linguistics book reviews, but English and Chinese linguistics book reviews show their own characteristics in terms of force and focus.…”
Section: Theoretical Foundation and Literature Review 21 Applied Resmentioning
confidence: 99%
“…(Martin & White, 2005) 2.2 Applied research on appraisal system As the appraisal system is very important to explore the interpersonal meaning of discourses, the appraisal system has gained wide attention from scholars at home and abroad since put forward. As one of the three subsystems of the appraisal system, the graduation system is also widely used in various discourses, such as academic discourses (Xie, 2017;Wang & Guan, 2016), debate discourses (Dong, 2012), literary texts (Fu & Fu, 2009), news discourses (Jiang & Xu, 2019), translation discourses (Munday, 2015;Shi & Gao, 2019), concession addresses (Li & Li, 2019). For example, Wang & Guan (2016) made a comparative analysis of graduation resources used in English and Chinese linguistics book reviews, and found that there are a large number of graduation resources in English and Chinese linguistics book reviews, but English and Chinese linguistics book reviews show their own characteristics in terms of force and focus.…”
Section: Theoretical Foundation and Literature Review 21 Applied Resmentioning
confidence: 99%
“…Graduasi force dapat dilihat pada kata yang bermakna kuantifikasi seperti 'billion', 'multiple' dan kata yang bermakna intensifikasi seperti pada kata 'the best' dan 'vital'( menunjukkan makna 'important' atau 'significant'). Li ( 2019) mengidentifikasi sarana graduasi di dalam pidato "Conssesion Addressee" calon presiden USA. Dalam penelitian tersebut ditemukan penanda graduasi untuk meyakinkan audiens seperti kata 'large'; dan frasa month after month.…”
unclassified
“…Secara leksikogramatikal, berdasarkan pada contoh kasus aspek graduasi di dalam sebuah teks yang disajikan oleh Martin dan White ( 2005) dan beberapa penelitian terdahulu (Crystalia & Sunardi, 2018;Fan, 2019;Li, 2019;Putri, 2019;Swear, 2015), elemen-elemen intensifikator terdiri dari elemen sirkumstansi (intensifier), epitet (noun atau adjective), dan elemen modalitas pada tataran frasa. Proses graduasi pada tataran frasa tersebut menunjukkan kombinasi endosentrik.…”
unclassified